2012 18th International ICE Conference on Engineering, Technology and Innovation 2012
DOI: 10.1109/ice.2012.6297678
|View full text |Cite
|
Sign up to set email alerts
|

The Application of an Assessment Tool for Lean Product Development: An exploratory study in Spanish Companies

Abstract: Lean practices have been applied by a diverse number of companies in manufacturing during the last decade. Nevertheless, the satisfactory and ongoing trajectory towards an effective application of Lean principles in the New Product Development Process (NPD) is currently under study as it is rather new in industry and the companies still face different challenges to successfully implement them. As a consequence, a novel Maturity Model and assessment tool called SMART has been developed as part of a Lean Transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…The Lean program proposes the simplification and reduction of formalization of the PDP (Haque & James-Moore, 2004;Cooper, 2009;Yan & Makinde, 2009;Sopelana et al, 2012). Improvements can be achieved through the application of Lean principles (Lean Thinking), related to the value stream identification, elimination of waste in PDP and the pursuit of perfection (Haque & James-Moore, 2004;Salgado et al, 2009;Khan et al, 2013;Tuli & Shankar, 2015).…”
Section: Programs In Pdpmentioning
confidence: 99%
See 2 more Smart Citations
“…The Lean program proposes the simplification and reduction of formalization of the PDP (Haque & James-Moore, 2004;Cooper, 2009;Yan & Makinde, 2009;Sopelana et al, 2012). Improvements can be achieved through the application of Lean principles (Lean Thinking), related to the value stream identification, elimination of waste in PDP and the pursuit of perfection (Haque & James-Moore, 2004;Salgado et al, 2009;Khan et al, 2013;Tuli & Shankar, 2015).…”
Section: Programs In Pdpmentioning
confidence: 99%
“…Companies also have used the Value Stream Mapping and other lean manufacturing tools in the PDP in order to eliminate waste and inefficiencies and maximize the value of the product developed (Yan & Makinde, 2009;Cooper, 2009;Sopelana et al, 2012;Tuli & Shankar, 2015;Tyagi et al, 2015). The literature in this area also brings few details on how the Lean can be used to improve the PDP, since the focus is on improving traditional manufacturing processes (Haque & James-Moore, 2004;Rossi et al, 2012;Khan et al, 2013).…”
Section: Programs In Pdpmentioning
confidence: 99%
See 1 more Smart Citation
“…O objetivo da melhoria do próprio PDP é buscar a sua eficiência e eficácia, sem retrabalho e desperdício de tempo em atividades que não agregam valor ao processo (Yan & Makinde, 2009;Kowang & Rasli, 2011). Para a melhoria do PDP podem ser empregadas ferramentas da abordagem Lean como o Mapa de Fluxo de Valor e eliminação de desperdícios (Cooper, 2009;Sopelana et al 2012), porém o uso destas ferramentas e práticas para a melhoria do PDP ainda permanece restrito (Rossi et al, 2012). As empresas procuram estratégias eficazes para melhorar a gestão do seu PDP, a fim de serem competitivas, pois a eficácia desse processo pode ser tão importante para a competitividade quanto os próprios produtos inovadores (Yan & Makinde, 2011).…”
Section: Quantidade De Publicações % Autoresunclassified
“…Upon reviewing the lean product development assessment literature and case studies, different assessment models and tools have been found for conducting the lean assessment including (Haque & Moore, 2004;Al-Ashaab et al, 2015;Mohammadi, 2010;Chase, 2000;Sopelana et al, 2012). However, no unique assessment model or tool identified can be said to fit all product development company.…”
Section: Lean Product Development Assessmentmentioning
confidence: 99%